Exercise Improves the Th1 Response by Modulating Cytokine and NO Production in BALB/c Mice - Terra, R.; Alves, P.J. F.; Gonçalves da Silva, S. A.; Salerno, V. P.; Dutra, P.M. L. (International Journal of Sports Medicine, 2013)
Physical exercise can improve health and may lead to changes in the functionality of the immune system. Moderate intensity exercise can reduce the risk of infection by shifting the overall immune response towards a T helper type 1 pattern. This study investigates the effect of 12 weeks of swimming on the cytokine profile of lymph node cells and macrophages and of the nitric oxide production by these cells. BALB/c mice were divided into 2 groups. The exercise group was subjected to swimming exercise. Lymph node cells culture showed that concentrations of interferon-γ and tumour necrosis factor-α were higher in the exercised group, while levels of interleukine-4 and interleukine-10 were significantly decreased in this group. The interleukine-10/interferon-γ ratio tended towards a T helper type 1 profile. Moreover, macrophages isolated from exercised mice produced more interleukine-12 and tumour necrosis factor-α following lipopolysaccharide stimulus. Challenging these macrophages with Leishmania major resulted in higher interleukine-12 production than was observed with macrophages from the control group. Nitric oxide production was increased in macrophages isolated from exercised group following lipopolysaccharide stimulus but not following infection with Leishmania major. These data suggest that exercise biases the immune system towards a T helper type 1 response profile.
Keywords: interleukine; leishmania; swimming; infection; immunologic system